2021
DOI: 10.1186/s12903-021-01894-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine regulates autophagy of human periodontal ligament cells through α7 nAchR that promotes secretion of inflammatory factors IL-1β and IL-8

Abstract: Background Nicotine is an important risk factor and the main toxic component associated with periodontitis. However, the mechanism of nicotine induced periodontitis is not clear. To investigated the mechanism through which nicotine regulates autophagy of human periodontal ligament cells (hPDLCs) through the alpha7 nicotinic acetylcholine receptor (α7 nAChR) and how autophagy further regulates the release of IL-1β and IL-8 secretion in hPDLCs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
5
0
2
Order By: Relevance
“…Studies have shown that nicotine may inhibit the production of inflammatory factors in oral epithelial cells, 35 while other studies have shown that nicotine can also be produce cytotoxicity to human periodontal cells and induce human periodontal cells to produce IL-1β and IL-8. 36 E-cigarettes are cytotoxic to a variety of cells, including gingival fibroblasts, gingival mesenchymal stem cells, and gingival epithelial cells, and affect cell proliferation, but e-cigarettes have less effect on cell proliferation and viability than tobacco. 37 Therefore, more in-depth research is needed to explore the safety of e-cigarettes and how they compare to tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nicotine may inhibit the production of inflammatory factors in oral epithelial cells, 35 while other studies have shown that nicotine can also be produce cytotoxicity to human periodontal cells and induce human periodontal cells to produce IL-1β and IL-8. 36 E-cigarettes are cytotoxic to a variety of cells, including gingival fibroblasts, gingival mesenchymal stem cells, and gingival epithelial cells, and affect cell proliferation, but e-cigarettes have less effect on cell proliferation and viability than tobacco. 37 Therefore, more in-depth research is needed to explore the safety of e-cigarettes and how they compare to tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…A nicotina, presente nos cigarros convencionais e eletrônicos, aumentou significativamente a autofagia das células do ligamento periodontal e estudos in vitro também mostram que o vaping tem um efeito prejudicial semelhante ao tabagismo na saúde do periodonto 8,28 .…”
Section: Discussionunclassified
“…Nessa perspectiva, a nicotina aumentou significativamente a autofagia das células do ligamento periodontal e a secreção dos fatores através do receptor nicotínico de acetilcolina, agravando, assim, a resposta inflamatória dos tecidos periodontais e, consequentemente, da periodontite. Portanto, os aerossóis dos cigarros eletrônicos são menos prejudiciais para os estreptococos comensais orais em comparação com a fumaça do cigarro convencional, mas os aromatizantes apresentam um efeito bactericida, matando os estreptococos, mas mantendo sua morfologia intacta, resultando em um prejuízo para o restante do micro bioma oral 28,29 .…”
Section: Discussionunclassified
“…This suggests that although nicotine is not a carcinogen and promotes the development of oral cancer through EGFR, P44/42 mitogen-activated protein kinase (ERK) and protein kinase B (AKT) [7]. Nicotine also significantly increased autophagy expression in human periodontal cells (hPDLC) via α7nAChR, which in turn regulated the liberation of inflammatory factors Interleukin-1β (IL-1β), and IL-8 from hPDLCs [8]. An in vitro study showed that a certain concentration of nicotine significantly inhibited the proliferation of oral epithelial cells and that nicotine concentration-dependently decreased the expression of Porphyromonas gingivalis lipopolysaccharide (P. gingivalis LPS) and TNF-α-induced cell surface expression of intercellular adhesion molecule-1 (ICAM-1).…”
Section: Composition Analysis Of Electronic Cigarettes and Traditiona...mentioning
confidence: 99%